Public Relations Functions for Sugar-Salt-Fat Consumption Control Programs Planning - Prita Suci Nurcandrani; Yudi Sudiana; Ayu May Lisa (Komunikator, 2021)
Non-Communicable Diseases such as stroke, diabetes mellitus, heart attack, and hypertension have increasingly lurked in Indonesia. The excessive consumption of sugar, salt, and fat (SSF) is the trigger for that case, and the government tries to take precautions for people from 13 to 18 years of age. Emphasizing on preventive health communication efforts, this study intended to assist the health promotion program of Puskesmas Purwokerto Utara 2 to apply Public Relations functions by providing IEC (Communication, Information, and Education) on controlling SSF in adolescents. This research used in-depth interviews and observations as data collection techniques, with qualitative descriptive methods to analyze the data. The result showed that this Puskesmas (district clinic) is identified as not implementing the SSF Control Program since its health promotion function is still more focused on routine programs. Meanwhile, 1.021 students in this work area need to prevent threatening diseases. Making collaboration with competent partners, Puskesmas may apply the functions of Public Relations in implementing the preventive programs by providing sufficient information about the danger of the excessive consumption of SSF, inviting people to change attitudes and actions, and representing the organization’s attitude towards society.